Improving the Legitimacy of Medicines Funding Decisions: A Critical Literature Review. (May 2015) - Pace, Jessica; Pearson, Sallie-Anne; Lipworth, Wendy
Many health care systems globally provide publicly subsidized access to prescribed medicines. Decisions about which medicines to fund affect a range of stakeholders, and it is not reasonable to expect that medicines funding decisions are supported by all stakeholder groups all the time. A more realistic aim may be for decisions to be understood and accepted as legitimate by stakeholders; however, several shortcomings of existing processes make it difficult to achieve this aim. To date, the main strategy to address these shortcomings has been to increase stakeholder involvement in decision making, either by eliciting stakeholder values or increasing stakeholder participation in decision making. Despite these efforts, there is growing evidence that decision makers are falling short when it comes to the perceived legitimacy of their resource allocation processes and decisions. As such, there is a pressing need for decision makers to think seriously and creatively about ways to increase the legitimacy of their processes and to make them more acceptable to a wider range of stakeholders. In this article we summarize and critique existing literature on the legitimacy of public resource allocation processes, and we make some practical suggestions for those who are concerned about this issue.